Not only Structured Query Language Method of Ad Request Processing - Nikolaiev, V.А.; Konashevych, O.I. (Электронное моделирование, 2017)
VertaMedia Company’s server provides operation of advertising exchange system between publishers (site’s owners), advertisers and intermediaries (SSP¹ and DSP² platforms). The objective of the system server is to process a request from a Publisher’s site as quickly as possible, choosing the most relevant advertisement campaign, to show it to a site’s user. The system works real-time online and as faster it makes accurate choice, the more likely that a user will see an advertisement. The obvious solution was to use relational database to compare the parameters of queries with the parameters and settings of ad campaigns, stored in this database. However, it turned out to be unsuitable as such system showed high latency. VertaMediaTM programmers have found an original way to process data, in which comparison occurred in a flat table using the hash sum and a binary tree for matching ad campaigns and another part of the request, which contained a set of keywords/tags was processed by Sphinx Search as local software solution. A method incorporates the original decision to work with database management systemless non-relational tables and use of specialized software solutions for matching keywords. It showed remarkable results in performance of a resource-intensive process, as described in detail in the article. Сервер компании VertaMedia обеспечивает работу рекламной системы обмена между издателями (владельцами сайтов), рекламодателей и посредников (SSP¹ и DSP²). Сервер системы должен обрабатывать запросы от сайтов издателей так быстро, насколько это возможно, выбирая наиболее подходящую рекламную кампанию, чтобы показать еe пользователю сайта. Система работает в реальном времени в интернете, и чем быстрее она делает точный выбор, тем больше вероятность того, что пользователь увидит рекламу. Очевидное решение состоит в использовании реляционных баз данных (БД) для сравнения параметров запросов с параметрами и настройками рекламных кампаний, которые хранятся в БД. Однако это оказалось недостаточно эффективным –– система показала высокую латентность. Программистами VertaMediaTM найден оригинальный способ обработки данных, когда сопоставления организованы в плоской таблице с помощью хеш сумм и бинарного дерева, а также локального программного решения Sphinx Search, которым обрабатываются ключевые слова и метки рекламных кампаний. Метод представляет собой оригинальное решение проблемы работы с нереляционными таблицами без системы управления БД с использованием специализированного программного решения для согласования ключевых слов. Полученные результаты свидетельствуют о значительном увеличении скорости при выполнении ресурсоемких процессов.